New Advances on Pathophysiology of Diabetes Neuropathy and Pain Management: Potential Role of Melatonin and DPP-4 Inhibitors - Busa, Prabhakar; Kuthati, Yaswanth; Huang, Niancih; Wong, Chih-Shung (Frontiers in Pharmacology, 2022)
Pre-diabetes and diabetes are a global epidemic, and the associated neuropathic complications create a substantial burden on both the afflicted patients and society. Diabetes mellitus (DM) leads to complications such as retinopathy, neuropathic pain, and neuroinflammation. Reductive and oxidative (Redox) stress levels imbalance and inflammation are chief components of the pathophysiology of DM complications. The various studies have been performed to detect the treatment for these neuronal complications, some of the therapeutic agents have investigated to treat these complications. The melatonin was among one of the drugs, which is a powerful antioxidant agent and an anti-inflammatory agent. In this present article, we review reports published in recent years on the therapeutic efficiency of melatonin in the treatment of DM neuronal complications. According to their findings there is a real prospect of using melatonin as supplementary dealing for hypoglycemic agents. This wide range complications an unbiassed analysis of advances and prospective vision of the paths to be used in an eventual therapeutic endorsement of melatonin in DM neuronal complications.